High-strength foamed concrete and preparation method thereof

By using zero-bleed foam and ultra-low water-cement ratio technology in foam concrete, combined with an appropriate amount of saturated water-reducing agent, the problems of low strength and poor mold filling of foam concrete are solved, and high-strength and low-cost products are achieved. Preparation of lightweight foam concrete.

CN116177969BActive Publication Date: 2025-01-21SHANGHAI CONSTR BUILDING MATERIALS TECH GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211705709.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-01-21
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing foam concrete has low strength and the cement slurry cannot be mixed into the foam under ultra-low water-adhesive ratio, which makes the mixture poor mold filling performance.

Method used

By adopting the technical solution of zero-bleeding foam and ultra-low water-to-cement ratio, the saturated dosage of water-reducing agent is determined to be 2.5%, and the water consumption is adjusted to ensure that the cement slurry can be evenly mixed with the foam at the ultra-low water-to-cement ratio and improve mixing. The mold filling property and strength of the material.

Benefits of technology

It is possible to prepare lightweight high-strength foam concrete with a compressive strength of 780-1020kg/m3 and a compressive strength of 7-11MPa at room temperature, reducing production costs and complexity and improving the strength and mold filling properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177969B_ABST
    Figure CN116177969B_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength foamed concrete. The high-strength foamed concrete is made of the following raw materials in parts by weight: 200-311 parts of cement, 39.4-61.29 parts of water, 5-7.78 parts of water reducer, and 12.44-14 parts of foam. The high-strength foamed concrete comprises cement, water, water reducer and foam, the foam comprises foaming agent and water for the foaming agent, the mass ratio of the foaming agent to the water for the foaming agent is 1:9, the water reducer is 2.5% of the mass of the gel material, the foam is 4%-7% of the mass of the cementitious material, and the water-to-binder ratio is 0.197; the cement is sulphoaluminate cement, the water reducer is a high-performance polycarboxylate water reducer, and the foaming agent is an animal foaming agent. The present invention achieves high strength through zero water bleeding foam and ultra-low water-binder ratio; in order to solve the problem that the cement slurry cannot be mixed into the foam and the mixture has poor mold filling property under the ultra-low water-binder ratio, the saturated dosage of the water reducer is fixed to 2.5% when the water-binder ratio is 0.2, and the water consumption is adjusted to avoid the problem that the cement slurry cannot be mixed into the foam and the mixture has poor mold filling property under the ultra-low water-binder ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to high-strength foam concrete and a preparation method thereof. Background Art

[0002] The frequent fires are caused by the fact that organic insulation materials in buildings are flammable and emit toxic gases, which can cause people to suffocate and die in a short period of time. As an ideal substitute for organic insulation materials, the composition of foamed concrete was fixed 10 years ago as cement, water, foaming agent, redispersible latex powder thickener, polypropylene fiber reinforcement, and calcium stearate waterproofing agent. However, as a brittle material, although foaming can give the material thermal insulation properties, the porous structure leads to low strength. Usually the density of foamed concrete is 300-800kg / m 3 When the compressive strength is 0.5-3.0MPa; different scholars have proposed different measures to strengthen foam concrete. One view is that quick-setting agents and early-strength agents can improve the early strength of foam concrete, thereby improving construction efficiency. One view is that tailings or admixtures can replace part of the cement and use the synergistic effect of multiple components to improve the strength of foam concrete. One view is that high-strength lightweight aggregates can improve the strength of foam concrete. One view is that laying transverse and longitudinal steel bars in the formwork frame and then pouring foam concrete in the cavity can improve the strength of the insulation material. One view is that the use of ultra-fine cement, fly ash, and silica fume can improve the strength of foam concrete.

[0003] CN113060991A Density 1000kg / m 3 , strength 10MPa. But it uses reinforcing fiber, reinforcing emulsion, foam stabilizer, water reducer, quartz sand, silica powder. Water reducer 0.1%-0.7%, water-binder ratio 0.1-0.25, foam dilution multiple 30-50, raw material cost is high, complex, contains organic components, not fireproof. Density 600-1600kg / m 3, strength 3.6-40MPa. In this patent, the cementitious material is 40% and the quartz sand is 60%, and the water requirement is much smaller than that of the cementitious material 100%. The gel material includes 40%-65% cement and 35%-60% admixture. The admixture includes 14%-25% volume stabilizer and 75%-86% mineral admixture. The admixture includes 14-25% volume stabilizer of its total amount. Below this value, the strength of the lightweight waterproof high-strength concrete decreases significantly. It can be seen that without adding the volume stabilizer, the strength decreases significantly. CN113060991A points out that the foaming agent content is too high, the foam bubble diameter is small, and it is difficult to disperse in actual production, resulting in low fluidity of the lightweight waterproof high-strength foam concrete, and large defective holes are easily generated inside during the pouring process. If the foaming agent content is too low, the foam stability will be reduced during stirring, and interconnected holes will be formed inside, affecting the waterproof performance; the bulk density of the lightweight waterproof high-strength foam concrete is also difficult to control, so that the distribution of the gel material, fine aggregate, reinforcing emulsion, reinforcing fiber and water reducer is more uniform, especially the fine aggregate and reinforcing fiber with skeleton support are evenly distributed. Correspondingly, the formed foam concrete material is more evenly stressed, reducing the risk of material fracture caused by excessive local stress and improving the strength of the material. CN113060991A adds water for mixing twice, 80% is added for the first time, and after adding the stabilizer, the remaining 20% ​​is added for the second time. The mixing water is added for the first time, so that the gel material, fine aggregate, reinforcing emulsion, reinforcing fiber and water reducer can better interact with each other during the dry and hard mixing process to achieve uniform dispersion and mutual penetration. Furthermore, in step (2), after the mixing water is added and stirred for the first time, the mixture of the gel material, fine aggregate, reinforcing emulsion, reinforcing fiber, water reducer and mixing water is stirred into a slurry, and the expansion of the mixture is 180-220 mm. The mixture with this expansion can make the foam easily dispersed into the slurry, and the foam stability is high, which is conducive to maintaining the quantity and shape of the foam. The ratio of CN113060991A gel material and mixing water is appropriate to avoid the presence of a large amount of surplus water, thereby reducing the shrinkage of concrete volume due to the evaporation of surplus water and solving the problems of concrete cracking, strength and durability and other performance degradation caused by the shrinkage of concrete volume.

[0004] In the absence of water reducer, the water-cement ratio must be as high as 0.4-0.7 to achieve good fluidity in order to mix into the foam. 30% fly ash has a light and high-strength effect, but fly ash has gradually become a scarce industrial by-product. Light aggregate vitrified microspheres, aerogels, hollow glass microspheres, and ceramsite have light and high-strength effects because the holes are prefabricated and the holes are more uniform and high-quality than those formed by foaming agents. However, they require high temperature or supercritical conditions for preparation, and the cost is much higher than that of foams with the same dosage. Large-scale applications in engineering are limited. Under the premise of the same performance, the fewer types of raw materials, the better. Some literatures have as many as 20 types of raw materials. Practical and systematic research on the mix ratio and preparation process of foamed concrete and improving the quality stability of foamed concrete are the development trends of inorganic thermal insulation materials. Other patents achieve thermal insulation performance through lightweight mineral admixtures and hollow fillers, while this patent only achieves thermal insulation performance through foaming agents. No filler reduces the water-cement ratio. Because fibers and thermal insulation fillers will increase the water-cement ratio. Do not put fibers and thermal insulation fillers to remove the side effects. Only by not adding polystyrene particles and not absorbing water can the water-cement ratio be reduced and the strength be improved. Since the strength can be improved by using an ultra-low water-cement ratio of 0.2, the reason for not using an ultra-low water-cement ratio is that the ultra-low water-cement ratio cannot be achieved by adding fine aggregates, high specific surface materials, and chemical foaming agents. Or the realization of the ultra-low water-cement ratio depends on a high amount of water-reducing agent, which will slow down the setting. Or under the condition of low water-cement ratio and high water-reducing agent dosage, the cement slurry is dry and hard and cannot be mixed into the foam, and the mold filling property of the mixture is poor. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a high-strength foamed concrete and a preparation method thereof. The high-strength foamed concrete and the preparation method thereof achieve high strength through zero water bleeding foam and ultra-low water-binder ratio; in view of the problem that cement slurry cannot be mixed into foam under ultra-low water-binder ratio and the mold filling property of the mixture is poor, the saturated dosage of the water reducer is determined to be 2.5% when the water-binder ratio is 0.2, and the water consumption is adjusted to avoid the problem that cement slurry cannot be mixed into foam under ultra-low water-binder ratio and the mold filling property of the mixture is poor.

[0006] In order to achieve the above invention purpose, the technical solution provided by the present invention is as follows:

[0007] A high-strength foamed concrete is made of the following raw materials in parts by weight: 200-311 parts of cement, 39.4-61.29 parts of water, 5-7.78 parts of water reducer, and 12.44-14 parts of foam; the high-strength foamed concrete comprises cement, water, water reducer and foam, the foam comprises foaming agent and water for the foaming agent, the mass ratio of the foaming agent to the water for the foaming agent is 1:9, the water reducer accounts for 2.5% of the mass of the gel material, the foam accounts for 4%-7% of the mass of the cementitious material, and the water-to-binder ratio is 0.197; the cement is sulphoaluminate cement, the water reducer is a high-performance polycarboxylate water reducer, and the foaming agent is an animal foaming agent.

[0008] A method for preparing high-strength foamed concrete, the method specifically comprising the following steps:

[0009] The first step is to determine the dilution multiple of the foaming agent for zero water seepage, and prepare the foaming agent dilution liquid according to the determined dilution multiple of the foaming agent;

[0010] The second step is to determine the saturated dosage of the water-reducing agent when the theoretical hydration is complete, i.e. the water-binder ratio is 0.2;

[0011] Step 3: Add cement and water reducing agent into the mixing pot according to the saturated dosage of water reducing agent determined in Step 2;

[0012] Step 4, preparing cement slurry, placing the mixing pot containing cement slurry and water reducing agent in Step 4 on a mixer fixed frame, measuring water of half the mass of cement in Step 4 and adding a part of the measured water into the mixer using a dropper, and obtaining cement slurry by stirring at a low speed with the mixer;

[0013] Step 5. After the cement slurry is prepared, let it stand in the mixing pot for 1 minute. When the water completely soaks the cement particles and the cement slurry becomes very thin, stop standing.

[0014] The sixth step is to prepare foam, wherein the foaming agent dilution prepared in the first step is preformed into uniform and continuous foam through an air compressor;

[0015] Step 7: Mixing foam: weigh the foam prepared in step 6 and add it to the mixing pot. The weighed foam is 4%-7% of the mass of the cementitious material. Stir the foam and cement slurry evenly until the mixed cement foam slurry is compact, self-absorbent and has good filling properties. Then stop stirring to obtain a homogeneous cement foam slurry.

[0016] In the eighth step, the cement foam slurry obtained in the seventh step is molded in a mold and demolded after 1 day, the foamed concrete after demolding is naturally cured to an age of 7-28 days, and the dry density and compressive strength of the foamed concrete are tested.

[0017] The dilution multiple of the foaming agent for zero water seepage in the first step is as follows: prepare foams with dilution multiples of 0, 10, 20, 30, 40, 50 and 60 times, and test the water seepage respectively. When the dilution multiple is 0, foam cannot be prepared. The water seepage of foams with dilution multiples of 10, 20, 30, 40, 50 and 60 times are 0mL, 4.7mL, 18.8mL, 32.4mL, 42.7mL and 61.2mL respectively. The dilution multiple of the zero water seepage foaming agent is 10 times.

[0018] The specific steps for determining the saturated dosage of the water-reducing agent when the theoretical hydration is complete, i.e., the water-binder ratio is 0.2 in the above second step are: 1000g of cement and 200g of water are prepared into cement slurry with a water-binder ratio of 0.2, and the expansion of the cement slurry is tested when the water-reducing agent dosage is 1%, 1.5%, 2%, 2.5% and 3%. When the water-reducing agent dosage is 1%, 1.5%, 2%, 2.5% and 3%, the tested cement slurry expansions are 89mm, 111mm, 139mm, 177mm and 152mm respectively, and the saturated dosage of the water-reducing agent is 2.5%.

[0019] The specific steps of obtaining cement slurry by low-speed stirring with a mixer in the fourth step are:

[0020] S41, when the mixer is stirring at a low speed, using a dropper to gradually add a weighed portion of water into the mixer, and when the cement slurry in the mixer is stirred into a petal shape, stop adding water;

[0021] S42, after the water addition is stopped, the mixer continues to stir for 30 seconds, and the mixer is turned off to observe the state of the cement slurry. When the cement slurry in the shape of petals immediately falls to the bottom of the mixer, and the cement slurry is thixotropic when stirred with a spatula, and the cement slurry is in a cohesive state when not stirred with a spatula, the stirring is stopped; otherwise, the mixer continues to stir until it meets the requirements;

[0022] S43, calculate the amount of water added to the mixer. Weigh the mass of the remaining water when the water addition stops, determine the amount of water used in this material state, and achieve the purpose of cement slurry being mixable and foamable at an ultra-low water-binder ratio and good filling properties of the mixture.

[0023] Based on the above technical solution, the high-strength foamed concrete and preparation method of the present invention have achieved the following technical effects through practical application:

[0024] 1. A preparation method of high-strength foam concrete of the present invention achieves high strength through zero-bleeding foam and ultra-low water-binder ratio; in view of the problem that cement slurry cannot be mixed into foam under ultra-low water-binder ratio and the mixture has poor mold filling property, by determining the saturated dosage of water reducer to be 2.5% when the water-binder ratio is 0.2, and adjusting the water consumption when the water reducer dosage is 2.5%, the problem that cement slurry cannot be mixed into foam under ultra-low water-binder ratio and the mixture has poor mold filling property is avoided.

[0025] 2. Zero water seepage foam ensures ultra-low water consumption. The saturated dosage of water reducer when the theoretical water requirement for complete hydration, i.e., the water-cement ratio of 0.2, is used to ensure the maximum water reduction rate. Stop adding water when the cement slurry is in the shape of petals to ensure that the slurry has cohesiveness at an ultra-low water-cement ratio. At this time, the water-cement ratio is 0.197, which is close to the theoretical water requirement for complete hydration of 0.2, and fluidity is obtained at the theoretical water-cement ratio for complete hydration. Stop stirring when the cement slurry is thixotropic, which ensures that the slurry has horizontal expansion ability at an ultra-low water-cement ratio. Let the cement slurry stand to allow the water to completely infiltrate the cement particles and the cement slurry to become thinner, ensuring that the foam can be mixed into the cement slurry. After hardening, it is light, strong, and does not fall off when drying. Stop stirring when the foam is mixed until the mixture is compact and self-absorbent, which ensures that the foam concrete has good mold filling and strong horizontal expansion.

[0026] 3. Foam has the effect of reducing density, and the strength reduction is greater than the density reduction. Reducing the dilution multiple of the foaming agent will significantly improve the strength. Determine the saturated dosage of the water-reducing agent when the theoretically fully hydrated water-cement ratio is 0.2, and the strength will be significantly improved. Stop adding water when the cement slurry is in the shape of petals, and the strength will be significantly improved. Stop stirring when the cement slurry is thixotropic, the strength will be significantly improved, and the density will be slightly reduced. Let the cement slurry stand for 1 minute, the strength will be significantly improved, and the density will be slightly reduced. The saturated dosage of the water-reducing agent, stop adding water when the cement slurry is in the shape of petals, and let the cement slurry stand for 1 minute, can ensure that the mixture is compact, self-priming and has good mold filling properties. The water-cement ratio is 0.197, and the water-reducing agent is 2.5%, and the strength is significantly improved. Foam reduces water consumption and increases strength compared to glass beads.

[0027] 4. The method for preparing high-strength foamed concrete of the present invention does not add accelerator and early strength agent, tailings or admixture, light aggregate, does not use multi-component synergistic effect and prefabricated holes, and only uses 4 kinds of raw materials to prepare 780-1020kg / m at room temperature. 3 , lightweight and high-strength foam concrete with a compressive strength of 7-11MPa, reduces production costs, simplifies production steps, and reduces production conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a picture of the thixotropy of the cement slurry in Example 1.

[0029] Figure 2 This is a picture of the cement slurry from Example 1 becoming thinner after being left standing.

[0030] Figure 3 This is a picture of the compact and self-absorbent cement foam mixture of Example 1.

[0031] Figure 4 This is a picture of the appearance of the foamed concrete in Example 1.

[0032] Figure 5 This is a picture of the foam concrete after compressive failure in Example 1.

[0033] Figure 6 This is a picture of the compact and self-absorbent cement foam mixture of comparative example 6.

[0034] Figure 7 This is the appearance picture of the foam concrete of Comparative Example 6.

[0035] Figure 8 This is the cement slurry of Comparative Example 7.

[0036] Fig. 9 This is a picture of the soft and weak cement foam mixture of Comparative Example 7.

[0037] Fig.10 This is the appearance picture of the foam concrete of Comparative Example 7.

[0038] Fig.11 This is a picture of the foam concrete of Comparative Example 7 after the compression test. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and effect of the present invention clearer, the present invention is described below by specific examples. However, it should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0040] like Figure 1-11 As shown, the present invention belongs to a high-strength foamed concrete, which is made of the following raw materials in parts by weight: 200-311 parts of cement, 39.4-61.29 parts of water, 5-7.78 parts of water reducer, and 12.44-14 parts of foam; the foam includes a foaming agent and water for the foaming agent, and the mass ratio of the foaming agent to the water for the foaming agent is 1:9; the gel material includes cement, water, a water reducer and foam, the water reducer is 2.5% of the mass of the gel material, the foam is 4%-7% of the mass of the cementitious material, and the water-cement ratio is 0.197; the cement is sulphoaluminate cement, the water reducer is a high-performance polycarboxylate water reducer, and the foaming agent is an animal foaming agent.

[0041] Example 1

[0042] A method for preparing high-strength foamed concrete, the method specifically comprising the following steps:

[0043] The first step is to determine that the dilution multiple of the zero-bleeding foaming agent is 10 times, weigh 600 g of the foaming agent, weigh 5400 g of the foaming agent water, and evenly mix the weighed foaming agent and the foaming agent water to obtain a foaming agent dilution solution;

[0044] The second step is to determine the saturated dosage of water reducer when the theoretical hydration is complete, i.e. the water-binder ratio is 0.2, which is 2.5%;

[0045] Step 3: weigh 200g of cement and add it to the mixing pot. Use a beaker to measure 5g of water reducer and add it to the same mixing pot.

[0046] Step 4: Prepare cement slurry. Place the mixing pot containing cement slurry and water reducing agent in Step 4 on the mixer fixed frame; measure 100g of water, keep the mixer stirring at a low speed, gradually add water to the mixing pot with a dropper, add water until the slurry is in the shape of petals when stirred, stop adding water, continue stirring for 30s, turn off the mixer and observe the state of the slurry. If the petal-shaped cement slurry immediately falls to the bottom of the mixing pot, it is thixotropic when stirred with a spatula, and the cement slurry is in a cohesive state without stirring with a spatula, then stop stirring; otherwise, continue stirring; weigh the remaining water mass to be 60.6g, then the water consumption is 100-60.6=39.4g;

[0047] Step 5. After the cement slurry is prepared, let it stand in the mixing pot for 1 minute. When the water completely soaks the cement particles and the cement slurry becomes very thin, stop standing.

[0048] The sixth step is to prepare foam, wherein the foaming agent dilution prepared in the first step is preformed into uniform and continuous foam through an air compressor;

[0049] The seventh step is to mix the foam. After the cement slurry is stirred and allowed to stand in the pot for 1 minute, 14 g of the foam prefabricated in the sixth step is weighed and added to the mixing pot. The weighed foam is 7% of the mass of the cementitious material. The foam and cement slurry are stirred and mixed evenly until the mixed cement foam slurry is compact, self-absorbent and has good filling properties. Then, the stirring is stopped to obtain a homogeneous and strong cement foam slurry.

[0050] In the eighth step, the cement foam slurry obtained in the seventh step is molded in a mold and demolded after 1 day, the foamed concrete after demolding is naturally cured to an age of 7-28 days, and the dry density and compressive strength of the foamed concrete are tested.

[0051] In the preparation process of the foamed concrete of this embodiment, the cement slurry is stirred until it has thixotropy. Figure 1 As shown. The cement slurry becomes thinner when it is left to stand. Figure 2 The cement foam paste mixture is stirred until it is compact and self-absorbent, see Figure 3 As shown. The hardened foam concrete is dry, light, strong and does not fall off. Figure 4 As shown. Foam concrete remains intact after compressive failure. Figure 5 shown.

[0052] The dry density of the foamed concrete in this embodiment is 779 kg / m 3The 7d compressive strength is 5.6MPa, and the 28d compressive strength is 7MPa. The strength of this embodiment increases significantly in the later period. The water-reducing agent is 2.5% and the water-cement ratio is 0.197, which does not slow setting. When demolded at 1d, the foam concrete is completely hardened. After the compressive test, it is still intact like ordinary concrete, indicating that the hydration product is connected to the dispersed phase, which can buy time for the evacuation of people when the building collapses suddenly.

[0053] Example 2

[0054] A method for preparing high-strength foamed concrete, the method specifically comprising the following steps:

[0055] The first step is to determine that the dilution multiple of the zero-bleeding foaming agent is 10 times, weigh 600 g of the foaming agent, weigh 5400 g of the foaming agent water, and evenly mix the weighed foaming agent and the foaming agent water to obtain a foaming agent dilution solution;

[0056] The second step is to determine the saturated dosage of water reducer when the theoretical hydration is complete, i.e. the water-binder ratio is 0.2, which is 2.5%;

[0057] Step 3: weigh 311g of cement and add it to the mixing pot. Use a beaker to measure 7.78g of water reducer and add it to the same mixing pot.

[0058] Step 4: Prepare cement slurry. Place the mixing pot containing cement slurry and water reducing agent in Step 4 on the mixer fixed frame; measure 155.5 g of water, keep the mixer stirring at a low speed, gradually add water to the mixing pot with a dropper, add water until the slurry is in the shape of petals when stirred, stop adding water, continue stirring for 30 seconds, turn off the mixer and observe the state of the slurry. If the petal-shaped cement slurry immediately falls to the bottom of the mixing pot, it is thixotropic when stirred with a spatula, and the cement slurry is in a cohesive state without stirring with a spatula, then stop stirring; otherwise, continue stirring; weigh the remaining water mass to be 94.21 g, then the water consumption is 155.5-94.21=61.29 g;

[0059] Step 5. After the cement slurry is prepared, let it stand in the mixing pot for 1 minute. When the water completely soaks the cement particles and the cement slurry becomes very thin, stop standing.

[0060] The sixth step is to prepare foam, wherein the foaming agent dilution prepared in the first step is preformed into uniform and continuous foam through an air compressor;

[0061] The seventh step is to mix the foam. After the cement slurry is stirred and allowed to stand in the pot for 1 minute, 12.44 g of the foam prefabricated in the sixth step is weighed and added to the mixing pot. The weighed foam is 4% of the mass of the cementitious material. The foam and cement slurry are stirred and mixed evenly until the mixed cement foam slurry is compact, self-absorbent and has good filling properties. Then, the stirring is stopped to obtain a homogeneous and strong cement foam slurry.

[0062] In the eighth step, the cement foam slurry obtained in the seventh step is molded in a mold and demolded after 1 day, the foamed concrete after demolding is naturally cured to an age of 7-28 days, and the dry density and compressive strength of the foamed concrete are tested.

[0063] The dry density of the foamed concrete in this embodiment is 1019 kg / m 3 , 7d compressive strength is 8.8MPa, and 28d compressive strength is 11MPa.

[0064] Comparative Example 1

[0065] The difference from Example 1 is that the dilution ratio of the foaming agent in the first step is 30 times.

[0066] The dry density of the foamed concrete of Comparative Example 1 is 765 kg / m 3 , compressive strength 4MPa; the dilution ratio of the foam agent changed from 10 times to 30 times, the foam changed from zero water seepage to 18.8mL water seepage, the density was equivalent, and the strength decreased from 7MPa to 4MPa, a decrease of 43%.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that the water-binder ratio in the second step is 0.25; that is, the saturated dosage of the water reducer is tested at a water-binder ratio of 0.25, and the results show that the water reducer dosage is 1%, 1.5%, 2%, 2.5%, and 3%, and the expansions are 114mm, 187mm, 154mm, 143mm, and 138mm, respectively, and the saturated dosage of the water reducer is 1.5%; accordingly, the "measure 5g of water reducer" in the fourth step is modified to "measure 3g of water reducer".

[0069] Results: In the fifth step, the appearance of petals in the cement slurry was the sign for stopping water addition. The water-binder ratio was 0.23 and the dry density of the foamed concrete was 768 kg / m 3 , compressive strength 4.2MPa. Density is equivalent, strength drops from 7MPa to 4.2MPa, a decrease of 40%.

[0070] Comparative Example 3

[0071] The difference from Example 1 is that the fourth step of "add water until the slurry forms petal shapes when stirred, then stop adding water" is modified to "add water until the slurry liquid surface is horizontal, then stop adding water".

[0072] The results showed that the water-binder ratio was 0.3. When demoulding at 4 days, the slow setting was serious, the foam concrete was soft and not hardened completely. 28d dry density 762kg / m 3 , compressive strength 3.4MPa.

[0073] Comparative Example 4

[0074] The difference from Example 1 is that the fourth step "If the petal-shaped cement slurry immediately falls to the bottom of the mixing pot, it is thixotropic when stirred with a spatula, and it is in a cohesive state without stirring with a spatula, then stop stirring" is modified to "If the petal-shaped cement slurry immediately falls to the bottom of the mixing pot and presents a horizontal liquid surface, then stop stirring".

[0075] As a result, the mixing time was too long, part of the foam broke and turned into water, the volume of the cement slurry decreased, and the slurry became thinner. The dry density of the foam concrete was 815kg / m 3 , compressive strength 3.7MPa.

[0076] Comparative Example 5

[0077] The difference from Example 1 is that the fifth step is deleted.

[0078] Results: At low water-cement ratio, the foam encounters dry and hard cement slurry, and partial defoaming occurs, and it is difficult to mix the cement slurry into the foam. The dry density of foam concrete is 827kg / m 3 , compressive strength 2.7MPa.

[0079] Comparative Example 6

[0080] The difference from Example 1 is that there is no water reducing agent in the second step and the water-binder ratio is 0.42.

[0081] Results The mixture was compact and self-absorbent at low water-cement ratio. Figure 6 However, after hardening, it was found that the cement foam mixture had poor mold filling properties and had holes. Figure 7 As shown. The dry density of foam concrete is 669kg / m 3 , compressive strength: 0.8MPa.

[0082] Comparative Example 7

[0083] The difference from Example 1 is that there is no water reducing agent in the second step and the water-binder ratio is 0.5.

[0084] The foamed concrete was demoulded in 1 day and hardened completely. It can be seen that in the foamed concrete, the cement paste with a water-binder ratio of 0.2 and a water reducer of 2.5% in Example 1 has a setting time equal to that of the cement paste with a water-binder ratio of 0.5 in Comparative Example 7; the dry density of this comparative example is 762kg / m 3 , 7d compressive strength 2.9MPa, 28d compressive strength 3MPa, the later strength almost no growth; compared with Example 1, the density is equivalent, the compressive strength is reduced from 7MPa to 3MPa, a decrease of 57%. Figure 8 Cement foam mix, see Fig. 9 As shown. Foam concrete hardener, see Fig.10 The test block was slag-free and all broke after the compression test. Fig.11 shown.

[0085] Comparative Example 8

[0086] The difference from Example 1 is that the foam weighed in step 7 is 11.2 g and the vitrified microspheres are 7.7 g. The foam density is 45.5 kg / m 3 , density of vitrified microspheres: 125kg / m 3 The difference between this comparative example and Example 1 is that 100% volume of foam is changed to 80% volume of foam + 20% volume of glass microspheres.

[0087] The water-binder ratio was adjusted to 0.35, and the dry density of the foamed concrete was 794 kg / m 3 , compressive strength 3.3MPa; the vitrified microspheres have a porous structure, and the water demand increases, resulting in the water-cement ratio increasing from 0.197 to 0.35. The density is equivalent, and the strength drops from 7MPa to 3.3MPa, a decrease of 53%.

[0088] The raw material composition, preparation method and performance of Example 1-Example 2 and Comparative Example 1-Comparative Example 8 are shown in Table 1. In combination with Example 1 and Example 2, the foam has the effect of reducing density, the density is reduced by 24%, and the strength is reduced by 36%. The reduction in strength is greater than the reduction in density. The lighter the foam concrete, the more the strength is reduced. In combination with Comparative Example 1 and Example 1, the strength is increased by 75% by reducing the dilution multiple of the foaming agent. In combination with Comparative Example 2 and Example 1, the saturated dosage of the water reducer is determined when the theoretically hydrated water-cement ratio is 0.2, and the strength is increased by 67%. In combination with Comparative Example 3 and Example 1, the cement slurry is petal-shaped and water is stopped, and the strength is increased by 119%. In combination with Comparative Example 4 and Example 1, the cement slurry has thixotropy and stops stirring, the strength is increased by 89%, and the density is reduced by 4%. In combination with Comparative Example 5 and Example 1, the cement slurry is left to stand for 1 minute, the strength is increased by 159%, and the density is reduced by 6%. Combining Comparative Example 6 with Example 1, the water reducing agent is saturated, the cement slurry is petal-shaped, and water is stopped. The cement slurry is left to stand for 1 minute, which can ensure that the mixture is compact, self-priming, and has good mold filling properties. Combining Example 1 with Comparative Example 7, the water-cement ratio is 0.197, the water reducing agent is 2.5%, and the strength is increased by 133%. Combining Example 1 with Comparative Example 8, the foam reduces water consumption by 44% compared with the glass beads, and the strength is increased by 112%.

[0089] Table 1

[0090]

[0091] This patent contains no fiber, no steel bar, no reinforcing material, no high-strength industrial solid waste, no lightweight aggregate, and no grinding. It uses the saturated dosage of water reducer under the theoretical hydration complete water-cement ratio, and takes adding water until the cement slurry is petal-shaped, stirring until the cement slurry has thixotropy, standing until the cement slurry becomes thin, and mixing and stirring until the mixture is compact and has self-absorption as the pre-judgment standards for the mixture. At room temperature, only 4 kinds of raw materials are used to prepare high-strength foam concrete with strong horizontal expansibility, strong filling capacity, good integrity after destruction, simple raw material components, low cost, and fire resistance.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A high-strength foamed concrete, characterized in that: The high-strength foamed concrete is made of the following raw materials in parts by weight: 200-311 parts of cement, 39.4-61.29 parts of water, 5-7.78 parts of water reducer, and 12.44-14 parts of foam; the foam is composed of a foaming agent and water for the foaming agent, the mass ratio of the foaming agent to the water for the foaming agent is 1:9, the water reducer is 2.5% of the mass of the cementitious material, the foam is 4%-7% of the mass of the cementitious material, and the water-cement ratio is 0.197; the cement is sulphoaluminate cement, the water reducer is a high-performance polycarboxylate water reducer, and the foaming agent is an animal foaming agent; The preparation method of the high-strength foamed concrete specifically comprises the following steps: The first step is to determine the dilution multiple of the foaming agent for zero water seepage, and prepare the foaming agent dilution liquid according to the determined dilution multiple of the foaming agent; The second step is to determine the saturated dosage of the water-reducing agent when the theoretical hydration is complete, i.e. the water-binder ratio is 0.2; Step 3: Add cement and water reducing agent into the mixing pot according to the saturated dosage of water reducing agent determined in Step 2; Step 4: prepare cement slurry. Place the mixing pot containing cement and water reducing agent in Step 3 on a mixer fixed frame. Measure water of half the mass of cement in Step 3 and add part of the measured water into the mixing pot using a dropper. Mix with the mixer at a low speed to obtain cement slurry. The specific steps of obtaining cement slurry by low-speed stirring with a mixer in the fourth step are: S41, while the mixer is stirring at a low speed, using a dropper to gradually add a portion of the weighed water into the mixing pot, and when the cement slurry in the mixing pot forms a petal shape during stirring, stop adding water; S42, after stopping adding water, the stirring pot continues to stir for 30 seconds, and the stirring pot is closed to observe the state of the cement slurry. When the cement slurry in the shape of petals immediately falls to the bottom of the stirring pot, and the cement slurry is thixotropic when stirred with a spatula, and the cement slurry is in a cohesive state when not stirred with a spatula, then the stirring is stopped; otherwise, the stirring pot continues to stir until it meets the requirements; S43, calculating the amount of water added to the stirring pot: weighing the mass of the remaining water when the water addition stops, and determining the amount of water used in this material state; Step 5. After the cement slurry is prepared, let it stand in the mixing pot for 1 minute. When the water completely soaks the cement particles and the cement slurry becomes very thin, stop standing. The sixth step is to prepare foam, wherein the foaming agent dilution prepared in the first step is preformed into uniform and continuous foam through an air compressor; Step 7: Mixing foam: weigh the foam prepared in step 6 and add it to the mixing pot. The weighed foam is 4%-7% of the mass of the cementitious material. Stir the foam and cement slurry evenly until the mixed cement foam slurry is compact, self-absorbent and has good filling properties. Then stop stirring to obtain a homogeneous cement foam slurry. In the eighth step, the cement foam slurry obtained in the seventh step is molded in a mold and demolded after 1 day, the foamed concrete after demolding is naturally cured to an age of 7-28 days, and the dry density and compressive strength of the foamed concrete are tested.

2. A method for preparing the high-strength foamed concrete according to claim 1, characterized in that: The method specifically comprises the following steps: The first step is to determine the dilution multiple of the foaming agent for zero water seepage, and prepare the foaming agent dilution liquid according to the determined dilution multiple of the foaming agent; The second step is to determine the saturated dosage of the water-reducing agent when the theoretical hydration is complete, i.e. the water-binder ratio is 0.2; Step 3: Add cement and water reducing agent into the mixing pot according to the saturated dosage of water reducing agent determined in Step 2; Step 4: prepare cement slurry. Place the mixing pot containing cement and water reducing agent in Step 3 on a mixer fixed frame. Measure water of half the mass of cement in Step 3 and add part of the measured water into the mixing pot using a dropper. Mix with the mixer at a low speed to obtain cement slurry. The specific steps of obtaining cement slurry by low-speed stirring with a mixer in the fourth step are: S41, while the mixer is stirring at a low speed, using a dropper to gradually add a portion of the weighed water into the mixing pot, and when the cement slurry in the mixing pot forms a petal shape during stirring, stop adding water; S42, after stopping adding water, the stirring pot continues to stir for 30 seconds, and the stirring pot is closed to observe the state of the cement slurry. When the cement slurry in the shape of petals immediately falls to the bottom of the stirring pot, and the cement slurry is thixotropic when stirred with a spatula, and the cement slurry is in a cohesive state when not stirred with a spatula, then the stirring is stopped; otherwise, the stirring pot continues to stir until it meets the requirements; S43, calculating the amount of water added to the stirring pot: weighing the mass of the remaining water when the water addition stops, and determining the amount of water used in this material state; Step 5. After the cement slurry is prepared, let it stand in the mixing pot for 1 minute. When the water completely soaks the cement particles and the cement slurry becomes very thin, stop standing. The sixth step is to prepare foam, wherein the foaming agent dilution prepared in the first step is preformed into uniform and continuous foam through an air compressor; Step 7: Mixing foam: weigh the foam prepared in step 6 and add it to the mixing pot. The weighed foam is 4%-7% of the mass of the cementitious material. Stir the foam and cement slurry evenly until the mixed cement foam slurry is compact, self-absorbent and has good filling properties. Then stop stirring to obtain a homogeneous cement foam slurry. In the eighth step, the cement foam slurry obtained in the seventh step is molded in a mold and demolded after 1 day, the foamed concrete after demolding is naturally cured to an age of 7-28 days, and the dry density and compressive strength of the foamed concrete are tested.

3. The method for preparing high-strength foamed concrete according to claim 2, characterized in that: Determining the dilution multiple of the foaming agent for zero water seepage in the first step is specifically as follows: preparing foaming agent dilution solutions with dilution multiples of 0, 10, 20, 30, 40, 50 and 60 times, and testing the water seepage respectively. When the dilution multiple is 0, foam cannot be prepared. The water seepage of foam with dilution multiples of 10, 20, 30, 40, 50 and 60 times are 0 mL, 4.7 mL, 18.8 mL, 32.4 mL, 42.7 mL and 61.2 mL respectively. Then the dilution multiple of the zero water seepage foaming agent is 10 times.

4. The method for preparing high-strength foamed concrete according to claim 2, characterized in that: The specific steps for determining the saturated dosage of the water-reducing agent when the theoretical hydration is complete, i.e., the water-binder ratio is 0.2 in the second step are as follows: 1000g of cement and 200g of water are prepared into a cement slurry with a water-binder ratio of 0.2, and the expansion of the cement slurry is tested when the water-reducing agent dosage is 1%, 1.5%, 2%, 2.5% and 3%. When the water-reducing agent dosage is 1%, 1.5%, 2%, 2.5% and 3%, the tested expansion of the cement slurry is 89mm, 111mm, 139mm, 177mm and 152mm respectively, and the saturated dosage of the water-reducing agent is 2.5%.

Citation Information

Patent Citations

  • Lightweight waterproof high-strength foam concrete and preparation method thereof

    CN113060991A

  • Ultra-light-weight foam concrete and manufacturing method of same

    CN102863193A

  • General purpose Portland cement based ultra-light physical foamed concrete

    CN104774033A